2012
DOI: 10.1371/journal.pone.0038729
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Adenosine Deaminase and Lymphocyte Proportion in Pleural Fluid for Tuberculous Pleurisy in Different Prevalence Scenarios

Abstract: BackgroundTuberculous pleural effusion (TPE) is a paucibacillary manifestation of tuberculosis, so isolation of Mycobacterium tuberculosis is difficult, biomarkers being an alternative for diagnosis. Adenosine deaminase (ADA) is the most cost-effective pleural fluid marker and is routinely used in high prevalence settings, whereas its value is questioned in areas with low prevalence. The lymphocyte proportion (LP) is known to increase the specificity of ADA for this diagnosis. We analyse the diagnostic usefuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…Of the 472 samples, 73 patients were diagnosed with TB pleural effusions (mean prevalence of 15.3%) [41]. They reported that the sensitivity and specificity of ADA in the diagnosis of pleural TB were 89% and 92.7%, respectively [40]. This was similar to the sensitivity and specificity reported in a recent meta-analysis of 63 studies (92% and 90%, respectively) [41].…”
Section: Adenosine Deaminasesupporting
confidence: 70%
See 1 more Smart Citation
“…Of the 472 samples, 73 patients were diagnosed with TB pleural effusions (mean prevalence of 15.3%) [41]. They reported that the sensitivity and specificity of ADA in the diagnosis of pleural TB were 89% and 92.7%, respectively [40]. This was similar to the sensitivity and specificity reported in a recent meta-analysis of 63 studies (92% and 90%, respectively) [41].…”
Section: Adenosine Deaminasesupporting
confidence: 70%
“…All patients with a fluid ADA level of greater than 70 U/L had TB, whereas no patient with a fluid ADA level of less than 40 U/L had TB pleuritis [39]. A recent study in Spain retrospectively looked at all consecutive patients with pleural effusion with a diagnostic thoracentesis at Mendaro Hospital from January 1998 to December 2008 [40]. The ADA levels had been determined in all samples.…”
Section: Adenosine Deaminasementioning
confidence: 99%
“…Many studies have suggested that pleural fluid adenosine deaminase (pfADA) is useful in the diagnosis of tuberculous pleural effusion (TBPE). [3][4][5][6][7][8][9][10][11][12][13] The merits of using pfADA include its low cost, short turnaround time, and high sensitivity and specificity. 3,12 Notwithstanding possibly better sensitivity and specificity for detecting TBPE by combining ADA1 or ADA2 in pleural fluid (PF) with other PF biomarkers such as tumour necrosis factor-alpha, interleukin 27, interferon-gamma and dipeptidyl peptidase IV, [14][15][16][17] it may not be cost-effective to combine pfADA with other PF biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The test performance of pfADA has largely been evaluated by including all cases with pleural effusion, and estimating its sensitivity and specificity with reference to an optimal cut-off value. Some studies fine-tuned the test performance by restricting the analysis to subjects with lymphocytic exudates 9,13 or to young adults. 21 In Hong Kong, pfADA has been measured centrally by the Chemical Pathology Laboratory at the Princess Margaret Hospital using the Diazyme commercial kit.…”
Section: Introductionmentioning
confidence: 99%
“…It affects mostly the children (elementary school age), the household and the individuals living in such an environment as a nursing home. It is common in those with personal hygiene deficiency because of self-infection [1,2].…”
Section: Introductionmentioning
confidence: 99%